Fundamentals of Neural Networks : Architectures, Algorithms, and Applications. - Fausett, Laurene ([s.l.] : PRENTICE HALL, 1994)
Written with the beginner in mind, this volume offers an exceptionally clear and thorough introduction to neural nets networks at an elementary level.
Keywords: COMPUTACION; ELECTRONICA; NEURAL NETWORKS (COMPUTER SCIENCE); REDES NEURONALES